Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
La plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Santé mentale chez les francophones en situation linguistique minoritaire - Bouchard, Louise; Colman, Ian; Batista, Ricardo (Reflets, 2018)
Bien que la plupart des études considèrent l’importance des déterminants sociaux sur l’existence des troubles mentaux, aucune ne désagrège les données en fonction de l’appartenance à une communauté de langue officielle en situation minoritaire, un fait pourtant reconnu pouvant avoir un impact sur la santé. L’incidence des langues et de la communication sur l’accès, la qualité et la sécurité des soins acquiert une portée plus grande dans le contexte canadien où coexistent deux langues officielles. Nous partons de cette prémisse pour dresser ici le portrait de la santé mentale de la population francophone vivant en situation linguistique minoritaire à partir des données de l’Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC, 2012)[1]. Mots-clés : santé et maladies mentales, francophones en situation minoritaire, Canada, Enquête de santé dans les collectivités canadiennes — Santé mentale (ESCC)

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Health profile of French-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H., & Mukaneza, A. (2018). Health profile of French-speaking minority communities in Canada [infographic]. University of Ottawa and Institut du savoir Montfort. fs-code-orig: Bouchard-2018d

Profil santé des communautés francophones en situation minoritaire au Canada [infographie] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)
fs-ref-orig: Bouchard, L., Sampasa-Kanyinga, H. et Mukaneza, A. (2018). Profil santé des communautés francophones en situation minoritaire au Canada [infographie]. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2018c